Концепция группового социального капитала и ее адаптация к отечественным условиям - Демкив, О. (Социология: теория, методы, маркетинг, 2005)
The author distinguishes three different levels of the social capital phenomenon interpretation, underlines a crucial role of the social network phenomenon for systemic vision of the social capital and analyses possibilities of application of social network analysis methodology to the study of social capital.